PEMBUATAN DAN KARAKTERISASI KATALIS ZnO/KARBON AKTIF DENGAN METODE SOLID STATE DAN UJI AKTIFITAS KATALITIKNYA PADA DEGRADASI RHODAMIN B - Septiani, Upita; Bella, Ilona; -, Syukri (Jurnal Riset Kimia, 2014)
Â ABSTRACTComposite catalyst ZnO/Activated Carbon (ZnO/AC) had been synthesized successfully bysolid state method. Synthesis was done by varying the addition of activated carbon (AC) 2%,5%, and 10% ZnO mass. Composite catalyst were calcinated at 400oC and characterized byFTIR (Fourier Transform Infra Red), XRD (X-Ray Diffraction), SEM (Scanning ElectronMicroscopy). Based on the results of FTIR, absorption appeared in the region wave number1400-1600 cm-1, which indicated stretching of C=C was assumed come from AC. From theXRD results, it was known by the addition of AC, not overly change the crystallinity and crystalsize of ZnO, the crystal structure is hexagonal (wurtzite). SEM images showed AC preventedthe agglomeration of ZnO that would expand the surface area of ZnO and increased catalyticactivity of ZnO. For the results of the catalytic activity test, catalyst ZnO/AC was tested on thedegradation of Rhodamine B solution (10 ppm) by UV light irradiation, where the increasingnumber of trains the catalytic ability of ZnO also increased, it could be concluded that activatedcarbon can support to increase the role of ZnO in degrading Rhodamine B.Keywords: composite catalyst, ZnO, activated carbon, solid state, Rhodamine B